A possible contribution of lipocalin‐2 to the development of dermal fibrosis, pulmonary vascular involvement and renal dysfunction in systemic sclerosis. (11th June 2015) - Takahashi, T.; Asano, Y.; Noda, S.; Aozasa, N.; Akamata, K.; Taniguchi, T.; Ichimura, Y.; Toyama, T.; Sumida, H.; Kuwano, Y.; Tada, Y.; Sugaya, M.; et al.
Summary: Background: Lipocalin‐2 is an adipocytokine implicated in apoptosis, innate immunity, angiogenesis, and the development of chronic kidney disease. Objectives: To investigate the role of lipocalin‐2 in systemic sclerosis (SSc). Materials and methods: Serum lipocalin‐2 levels were determined by enzyme‐linked immunosorbent assay in 50 patients with SSc and 19 healthy subjects. Lipocalin‐2 expression was evaluated in the skin of patients with SSc and bleomycin (BLM)‐treated mice and in Fli1‐deficient endothelial cells by reverse transcriptase‐real time polymerase chain reaction, immunoblotting and/or immunohistochemistry. Results: Although serum lipocalin‐2 levels were comparable between patients with SSc and healthy controls, the prevalence of scleroderma renal crisis was significantly higher in patients with SSc with elevated serum lipocalin‐2 levels than in those with normal levels. Furthermore, serum lipocalin‐2 levels inversely correlated with estimated glomerular filtration rate in patients with SSc with renal dysfunction. Among patients with SSc with normal renal function, serum lipocalin‐2 levels positively correlated with skin score in patients with diffuse cutaneous SSc with disease duration of < 3 years and inversely correlated with estimated right ventricular systolic pressure in total patients with SSc. Importantly, in SSc lesional skin, lipocalin‐2 expression was increased in dermal fibroblasts and endothelial cells. In BLM‐treated mice, lipocalin‐2 was highly expressed in dermal fibroblasts, but not in endothelial cells. On the other hand, the deficiency of transcription factor Fli1, which is implicated in SSc vasculopathy, induced lipocalin‐2 expression in cultivated endothelial cells. Conclusions: Lipocalin‐2 may be involved in renal dysfunction and dermal fibrosis of SSc. Dysregulated matrix metalloproteinase‐9/lipocalin‐2‐dependent angiogenesis due to Fli1 deficiency may contribute to the development of pulmonary arterial hypertension associated with SSc. Abstract : What's already known about this topic? Adipokines have been shown to play various important roles in systemic sclerosis (SSc). Lipocalin‐2 is a member of the adipokines, which are implicated in apoptosis, innate immunity, angiogenesis, and the development of chronic kidney disease. What does this study add? Lipocalin‐2 potentially contributes to the development of skin sclerosis, pulmonary arterial hypertension and renal damage in SSc, further supporting the critical roles of adipokines in the pathogenesis of this disease.